Going beyond Citations: SERUM — a new Tool Provided by a Network of Libraries - Gorraiz, Juan; Gumpenberger, Christian (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
Citation metrics are a well-established means to assess the impact of scholarly output. With the growing availability of e-journals, usage metrics have become an interesting alternative to citation metrics; they allow for viewing scholarly communication from the user’s perspective. Usage metrics offer several advantages that have the potential of enhancing existing evaluation criteria for scholarly journals. This paper suggests an approach to providing global usage metrics which is supported by libraries. The goal is to provide an analytical tool called Standardized Electronic Resource Usage Metrics (SERUM) which is comparable to the Journal Citation Reports (JCR), but which makes use of download data instead of citation data. Global download data would be obtained from the publishers, assuming they are willing to contribute in order to benefit from newly established evaluation criteria for periodicals beyond the Journal Impact Factor (JIF) and consequential strengthening of their products. An international network of libraries with a sound disciplinary coverage will be established in order to obtain, manage and check the authenticity of the data delivered by the publishers. The network will act as a clearing centre operated by independent information specialists to guarantee data integrity as well as data curation according to a standardised format. Furthermore, the network’s internationally distributed members should also track and manage local usage data, reflect local trends, and relate these to the global publishers’ data. In addition, a regularly updated version with specific basic usage metrics and journal rankings will be offered.